PENDIDIKAN ISLAM DALAM KONTEKS PENDIDIKAN NASIONAL - Muhamad Ryan, Deni; Taufik Kurahman, Opik (As-Sulthan Journal of Education, 2025)
This research examines the reconstruction of Islamic Education within the framework of national education, focusing on philosophical, axiological, digital, and multicultural dimensions. The study highlights the need for Islamic Education to adopt a humanistic-transformative paradigm to address contemporary challenges. Additionally, it emphasizes the importance of digital religious literacy and the integration of wasathiyah and Adab values into an inclusive and adaptive educational system. This article proposes a conceptual model for curriculum development and Islamic educational practice in Indonesia.